Our Homes: An inclusive study about what moving house is like for people with intellectual disabilities in Ireland. (24th October 2018) - Salmon, Nancy; Garcia Iriarte, Edurne; Donohoe, Brian; Murray, Laura; Singleton, Greg; Barrett, Mary; Dillon, Marie
Accessible Summary: The Inclusive Research Network (IRN) is a group of researchers who do projects that matter to people with intellectual disabilities in Ireland. This paper is about a project we did to learn what it is like for people with intellectual disabilities in Ireland to move from one house to another. We talked to 35 people who moved house. Some people chose where to move but others had no choice. Feeling safe made them happier in their new home. One third of the people we spoke to had no choice about where they live and who they live with. Having these choices is their right under the United Nations Convention on the Rights of Persons with Disabilities. People with intellectual disabilities need supporters who listen and respect them. Abstract: Background: Supporting people with intellectual disabilities to live well in communities they choose is deinstitutionalisation's central aim and endorsed by the United Nations Convention on the Rights of Persons with Disabilities (CRPD) (UN, 2006). This study focused on the experiences of people with intellectual disabilities in Ireland when moving home using an inclusive research approach. Method: This inclusive research project employed a qualitative approach. Participants included 19 men and 16 women (total n  = 35) with ages ranging from 22 to 77 years. Structured interviews attended to the experience of moving home and the supports accessed during and after the transition to community living. Results: Thematic analysis yielded four themes: "expressing choice" in the moving process; "feeling connected or isolated when moving"; "accessing supports during and after the move"; and finally, participants' reflections on "experiencing vulnerability and feeling safe" while resettling. Conclusions: This is the first study about people with intellectual disabilities moving home to be collaboratively designed and completed by an inclusive research team. Although much is understood about the long‐term benefits of engaging in meaningful choices about housing and supports, concerns remain about the extent to which the will and preferences of people with intellectual disabilities in Ireland are respected when moving home.